The Normativity Problem as a Serious Obstacle to Modelling Gender (Aporia, 2018)
In this paper, I explore Sally Haslanger’s (2000) proposed approach to modelling gender which she intends to overcome several problems for such a project. I specifically focus on what Haslanger calls the normativity problem, in which definitions meant to overcome oppression only reinforce oppressive norms. I argue that the normativity problem is a serious one for defining gender and that Haslanger does not successfully overcome it with her definitions of man and woman. In §§1 and 2, I offer background for and explain her account of the problem before offering my own formal reconstruction of it as what I call the normativity argument that (a) we ought not marginalise individuals in our defining of social categories, (b) definitions encouraging normative behaviour do this, and (c) any model of gender encourages such behaviour. In §3 I then give an account of her proposed definitions of man and woman along with her theoretical objections to the normativity argument—suggesting that only certain kinds of marginalisation are undesirable within the constraints of a particular feminist project and that her definitions do not encourage normative behaviour. I then offer my responses to her objections in §4, suggesting that her definitions are normative and do marginalise in a way incongruous even with her particular feminist project. Before concluding, I briefly discuss in §5 where my criticisms of Haslanger’s approach to defining gender fit into some existing criticisms, in order to give my position an even clearer shape. This paper concludes in §6 by sketching some possible ways forward in the philosophy of gender responding to this problem.